Developing English Front Office Materials for Twelve Grade Students in First Semester - Pratama, I Gede Febry Wira; Wedanthi, Nyoman Karina; Dewi, Kadek Sintya; Budasi, I Gede (The Art of Teaching English as a Foreign Language (TATEFL), 2021)
The purpose of this study was to develop English front office materials for first semester students of class XII at SMK N 2 Singaraja. In the data collection process, researchers used six instruments, namely, Google form for teachers and students, Questionnaire for teachers and front office staff, Checklist for students, and the last instrument is Checklist for expert judges. This research method used the Design and Development (D&D) model. The results showed that there were 5 topics that needed to be developed, namely; Handling guest arrivals and departures, Handling guest baggage, Bell desk service handling requests, Individual guest check-in handling, Individual guest check-out handling. The conclusion obtained in this study is that there are 5 topics that must be developed into products and each topic contains input, content focus, language focus, and task and the product quality is classified as very good based on the results of two expert judges.